Faktor-faktor yang Berhubungan dengan Kepatuhan Diet pada Penderita Diabetes Melitus Tipe 2 - Zulfahmi Zulfahmi; Syahrul Syahrul; Andina Setyawati (Journal of Telenursing (JOTING), 2023)
This study aims to determine the factors that influence dietary compliance in people with type 2 diabetes mellitus (DM) as a whole using the methods used: descriptive study, qualitative study, cross-sectional survey. There were seven articles that met the inclusion criteria. The average age of the sample in the articles obtained ranged from 18 to 70 years. In conclusion, the factors found to influence diet compliance were knowledge factors about eating patterns, physical activity factors, access to information factors, social support factors, motivation and self-ability factors, perception factors, income factors, age factors, and environmental and cultural factors. Keywords: Diabetes Mellitus, Compliance, Diet